Pengaruh Koordinasi terhadap Efektivitas Penanggulangan HIV/AIDS Kabupaten Sumedang - Irma Hermayanty; Dhesti Widya Nurhasanah Ningrum (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2019)
This study aims to determine how much influence coordination of the effectiveness of HIV/AIDS prevention in Sumedang District. This research method use is Descriptive analysis and the data collection techniques were conducted using literature study techniques and field study techniques. Population in this research are HIV/AIDS prevention commision officer and people of AIDS Citizen Cadres in totally 19 peoples. To test the research hypothesis used analysis techniques, which are by Percentage Calculation, Spearman Rank Coefficient Test, Significance Test, and Determinarion Coefficient Test. The result of research and statistical calculation on the proposed hypotheesis, can be concluded that there is any influence coordinating between HIV/AIDS prevention commission officer with AIDS Citizen Cadres on the effectiveness of HIV/AIDS prevention program achievement in Sumedang by 47,2%.